Pengaruh Kualitas Produk Dan Harga Terhadap Pembelian Baju Bekas Atau Thrift Di Pasar Senen Jakarta Pusat - Muhammad Rafly; Hadita Hadita (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
As we know, shopping for used or thrift goods has become a culture for all people, both young and old, so it has become a fashion trend culture in this era. This article aims to find out how product quality and price influence the purchase of used/thrift clothes at the Senen market in Central Jakarta. . Through the descriptive technique research method which produces results that are influential through the tests that have been carried out, there are still many shortcomings in the writing. It would be better for the writer to need criticism or suggestions for further writing. The research results are that product quality and price greatly influence the purchase of used clothes.